A back-door brain drain - Oded Stark; Lukasz Byra (University of Bonn, Center for Development Research (ZEF), 2012)
In this paper we study the impact of the international migration of unskilled workers on skill formation and the average skill level in the home country. We analyze what appears to be the least threatening scenario from the point of view of its effect on the supply of skills at home: namely, migration exclusively by unskilled workers. Somewhat surprisingly, we find that even without the departure of skilled workers, the home country suffers reduced aggregate skill formation. Although as a response to a higher wage rate per unit of human capital in the new equilibrium skilled workers choose to accumulate more human capital than before the opening up to migration of unskilled workers, the number and share of skilled workers in the home country's workforce fall. The combined effect is a decrease in the average level of human capital in the home country.
Keywords: F22; J24; O15; 330; Migration of unskilled workers; Human capital formation; Depletion of human capital; Ungelernte Arbeitskräfte; Internationale Wanderung; Bildungsinvestition; Brain Drain; Theorie